Measuring the concordance between endoscopic and histologic inflammation and its effect on IBD-associated dysplasia - Guerrero Vinsard, Daniela; Lennon, Ryan; Avvaru, Himaja Kumari; Patel, Mehrie; Lahori, Simmy; Raffals, Laura E.; Coelho-Prabhu, Nayantara (Endoscopy International Open, 2024)
Background and study aims Chronically inflamed colonic mucosa is primed to develop dysplasia identified at surveillance colonoscopy by targeted or random biopsies. We aimed to explore the effect of mucosal inflammation on detection of visible and “invisible” dysplasia and the concordance between the degree of endoscopic and histologic inflammation.Patients and methods This was a 6-year cross-sectional analysis of endoscopic and histologic data from IBD. A multinomial model was created to estimate the odds for a specific lesion type as well as the odds of random dysplasia relative to the degree of inflammation. Kappa statistics were used to measure concordance between endoscopic and histologic inflammation.Results A total of 3437 IBD surveillance colonoscopies between 2016–2021 were reviewed with 970 procedures from 721 patients containing 1603 visible lesions. Kappa agreement between histologic and endoscopic degree of inflammation was low at 0.4. There was a positive association between increased endoscopic inflammation and presence of tubulovillous adenomas (TVAs) (odds ratio [OR] 2.18; 95% confidence interval [CI] 1.03–4.62; P=0.04). Among cases with visible lesions, the yield of concomitant random dysplasia was 2.7% and 1.9% for random indefinite dysplasia. The odds of random dysplasia significantly increased as the degree of endoscopic and histologic inflammation increased (OR 2.18, 95%CI 1.46–3.26; P<0.001 and OR 2.75; 95%CI 1.65–4.57, P<0.001, respectively. The odds of indefinite random dysplasia also significantly increased as endoscopic and histologic inflammation increased (OR 2.90; 95%CI 1.85, 4.55, P<0.001 and OR 1.98; 95%CI 1.08, 3.62, P<0.035, respectively.Conclusions Endoscopic and histologic inflammation are associated with higher odds of finding TVAs and random low-grade, high-grade, and indefinite dysplasia. Concordance between histologic and endoscopic inflammation severity is low.
Keywords: Inflammatory bowel disease; Diagnosis and imaging (inc chromoendoscopy, NBI, iSCAN, FICE, CLE...)